Variation in Associations Between Family Dinners and Adolescent Well‐Being. Issue 1 (February 2014) - Meier, Ann; Musick, Kelly
<x xml:space="preserve">Abstract</x> Empirical evidence and conventional wisdom suggest that family dinners are associated with positive outcomes for youth. Recent research using fixed‐effects models as a more stringent test of causality suggests a more limited role of family meals in protecting children from risk. Estimates of average effects, however, may mask important variation in the link between family meals and well‐being; in particular, family meals may be more or less helpful based on the quality of family relationships. Using 2 waves of the National Longitudinal Study of Adolescent Health (N = 17, 977), this study extended recent work to find that family dinners have little benefit when parent–child relationships are weak but contribute to fewer depressive symptoms and less delinquency among adolescents when family relationships are strong. The findings highlight the importance of attending to variation when assessing what helps and what hurts in families.